Report on Local Government Finances Determinants: Evidence from Stewardship Perspectives - Sasya Razita Fahira; Siti Musyarofah (Master of Accounting Universitas Trunojoyo Madura, 2023)
This study aims to provide empirical findings regarding the determinants of the level of reports of local government finance disclosure in districts/cities in East Java province. Determinants of the level of reports of local government finance disclosure include regional characteristics, complexity, and audit findings which are broken down into independent variables, including regional wealth, level of dependence, total assets, number of local government agencies, population, number of findings, and level of irregularities. The sample in this study was 93 reports on local government finances audited by the Audit Board of the Republic of Indonesia representing East Java Province for the 2017-2019 period (3 years), which were obtained using the purposive sampling method. The analytical method uses multiple linear regression analysis. The results showed that regional wealth and the level of dependence had a negative effect. Total assets positively affected the level of disclosure of financial statements. At the same time, the number of local government agencies, population, number of findings, and level of irregularities did not significantly affect the financial reports of district/city regional governments in East Java province. The central government needs to encourage regional financial transparency, especially for regions with a high local revenue and dependency level.